Dryinidae species (Hymenoptera, Aculeata) in the semiarid region of Bahia, Brazil - Santos, Maria Felícia Melo (2024)
Dryinidae is a family of parasitoids and predators; it is the third largest family in the superfamily Chrysidoidea, with 1,924 species worldwide. The diversity of this family may be even greater, but studies on its diversity and geographical distribution are scarce, especially in semiarid regions. The objective of this study was to describe the occurrence and diversity of Dryinidae genera in the Semiarid region of Bahia, Brazil. Five Malaise traps were distributed in two areas with native vegetation and in one with eucalyptus (Eucalyptus urophylla) plantation and monitored monthly for two years. Specimens were identified to genus and morphospecies levels. The collection consisted of 77 Dryinidae specimens from four subfamilies (Anteoninae, Aphelopinae, Dryininae, Gonatopodinae), seven genera (Anteon Jurine, 1807; Aphelopus Dalman, 1823; Crovettia Olmi, 1984; Deinodryinus, Perkins, 1907; Dryinus Latreille, 1804; Gonatopus Ljungh, 1810 and Thaumatodryinus Perkins, 1905), and 29 morphospecies. The genus Dryinus was the most frequent in the three study areas. Areas with native vegetation, mainly the forest area, showed greater diversity than the area with eucalyptus trees. This study contributes with data of identification and distribution of Dryinidae species in the Semiarid region of the state of Bahia, Brazil.